Improvement in social and cognitive functioning associated with paliperidone extended-release treatment in patients with schizophrenia: a 24-week, single arm, open-label study - Shi C; Yao S; Xu Y; Shi J; Xu X; Zhang C; Jin H; Yu X (Neuropsychiatric Disease and Treatment)
Chuan Shi,1–4 Shu Qiao Yao,5 Yi Feng Xu,6 Jian Guo Shi,7 Xiu Feng Xu,8 Cong Pei Zhang,9 Hua Jin,10 Xin Yu1–4 1Clinical Research Center, Peking University Sixth Hospital, 2Clinical Research Center, Peking University Institute of Mental Health, 3Key Laboratory of Mental Health, Ministry of Health (Peking University), 4National Clinical Research Center for Mental Disorders (Peking University Sixth Hospital), Beijing, 5Clinical Center of Psychology, The Second Xiangya Hospital, Central South University, Changsha, Hunan Province, 6Department of Psychiatry, Institute of Mental Health, Shanghai Jiao Tong University, Shanghai, 7Department of Psychiatry, Xi’an Mental Health Center, Xian, Shanxi Province, 8Department of Psychiatry, The First Affiliated Hospital of Kunming Medical School, Kunming, Yunnan Province, 9Department of Psychiatry, The First Haerbin Psychiatric Hospital, Haerbin, Heilongjiang Province, People’s Republic of China; 10Department of Psychiatry, University of California at San Diego, La Jolla, San Diego, CA, USA Purpose: This single-arm, open-label study aimed to explore the effects of extended-release paliperidone on social and cognitive function in patients with schizophrenia.Methods: Paliperidone extended-release (flexible dose ranging from 3 to 12 mg/day orally) was administered for 24 weeks in patients with schizophrenia. Patient function was assessed using the personal and social performance scale, measurement and treatment research to improve cognition in schizophrenia initiative-consensus cognitive battery, positive and negative syndrome scale, and clinical global impression-severity.Results: Ninety patients were included in the full analysis set, while 72 patients were included in the per protocol set. The personal and social performance score was 54.3±14.3 at baseline, and significantly increased to 73.4±12.6 at week 24 (P<0.001). For the measurement and treatment research to improve cognition in schizophrenia initiative-consensus cognitive battery assessment, six of the nine individual subtests, six of the seven cognitive domains, and total cognitive scores improved significantly (P<0.05) between baseline and endpoint. positive and negative syndrome scale total scores and clinical global impression-severity scores decreased gradually (P<0.001) from week 4 to the conclusion of the study.Conclusion: Paliperidone extended-release treatment significantly improves social and neurocognitive function as well as symptoms in Chinese patients with schizophrenia. Keywords: paliperidone, schizophrenia, neurocognition, social function